2011
DOI: 10.4103/0975-1475.92152
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination using mesiodistal dimension of permanent maxillary incisors and canines

Abstract: Background:Sexual dimorphism refers to the differences in size, shape, etc., between males and females. The dentition's use in sex assessment has been explored and advocated owing to its strength and resistance to peri- and post-mortem insults.Objectives:The study evaluated permanent maxillary incisors and canines for sexual dimorphism and estimated the level of accuracy with which they could be used for sex determination.Materials and Methods:The study was conducted on 100 subjects (50 males, 50 females). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 14 publications
6
52
2
8
Order By: Relevance
“…These percentages were higher than of Khangura et al (5) . While for right central incisor, the percenatges were 56.5, 67 and 61.7% respectively.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…These percentages were higher than of Khangura et al (5) . While for right central incisor, the percenatges were 56.5, 67 and 61.7% respectively.…”
Section: Resultscontrasting
confidence: 52%
“…Many researches were done to identify the genders using the maxillary and mandibular canines. They depended on the mesio-distal dimension of these teeth (5,6) and in many articles on the intercanine width in addition to the mesio-distal width to get the canine index and standard canine index (2,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) . Other researches studied the bucco-lingual dimension of teeth (18,19) , height of tooth (3) and permanent maxillary first molar (20) as a base for gender identification.…”
Section: Introductionmentioning
confidence: 99%
“…Sanin and Savara studies reported the differences in the crown size patterns and even Khangura et al found that the mesiodistal width of teeth in males are greater when compared to females in their study. [9] Various teeth were considered in most of the studies, but our study aimed at the sexual dimorphism in mandibular first molars in Iranian population considering the diagonal facial and occlusal measurements. Odontometric parameters can be used in larger and different populations for sex determination as it is simple to perform, reliable material, inexpensive, and easy procedure to measure the parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in 1920, a formula that estimates physical stature was created from the proportion of the lateral dimensions of the crowns of the lower incisors and canines [23]. Moreover, an analysis of mandibular canine dimensions was thought to show the presence of sex dimorphism [24].…”
Section: Findings and Discussion Of Mr Lloyd's Reportmentioning
confidence: 99%